2006
DOI: 10.1002/joc.1461
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of New Zealand's climate using a high‐resolution nested regional climate model

Abstract: Abstract:A regional climate model (RCM) for New Zealand has been developed. The RCM is embedded within a GCM and both models are run under pre-industrial conditions. Seasonal mean output of the RCM is compared against NCEP data and the New Zealand national climate database. Regional and seasonal aspects of modelled surface temperature and precipitation are to a large extent simulated correctly. The main anomalies are related to the difficulty of incorporating New Zealand's orography appropriately and to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…during the last glacial maximum; Drost et al, 2007;Ackerley et al, 2011) may alter empirical relationships (i.e. TIMs) informed during the present climate, altering the climate signals derived from glacier fluctuations.…”
Section: Implications For Modelling Glacier-climate Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…during the last glacial maximum; Drost et al, 2007;Ackerley et al, 2011) may alter empirical relationships (i.e. TIMs) informed during the present climate, altering the climate signals derived from glacier fluctuations.…”
Section: Implications For Modelling Glacier-climate Interactionsmentioning
confidence: 99%
“…Given that this synoptic variability is closely linked to inferred changes in cloudiness as well as air mass properties (Hay and Fitzharris, 1988), and that these synoptic controls are thought to have varied over palaeoclimatic timescales (Drost et al, 2007;Ackerley et al, 2011), it is vital that the influence of clouds on SMB is separated out from the influence of air mass properties (in particular air temperature). Recent field studies on Brewster Glacier in the Southern Alps, have shown the high frequency of cloudy conditions during all seasons (> 50 % overcast conditions) as well as the significant and variable effect of clouds on SW↓, LW↓, and net radiation (Rnet) .…”
Section: Introductionmentioning
confidence: 99%
“…The RCM domain spans 32 to 52 • S and 160 to 193 • E (167 • W) on a regular rotated grid with a horizontal resolution of 0.27 • and with the North Pole at 48 • N and 176 • E. Such a rotated grid, with the equator running through the New Zealand domain, ensures a quasi-uniform grid box spacing. The 0.27 • resolution results in a domain of 75 × 75 grid points, reduces computation time for long simulations, and has been shown to be adequate in previous studies (Drost et al, 2007). The spatial resolution necessitates a computational time step of 3 min.…”
Section: Introductionmentioning
confidence: 97%
“…to quantitatively establish the relationship between the change in annual mean global mean surface temperature and the change in the climate variable of interest and its variability. RCM simulations used in this study were performed using the Hadley Centre RCM HadRM3-PRECIS (Jones et al, 2004) that has been modified to be used for New Zealand (Bhaskaran et al, 1999(Bhaskaran et al, , 2002Drost et al, 2007) and which is described in further detail in Mullan et al (2016). The RCM domain spans 32 to 52 • S and 160 to 193 • E (167 • W) on a regular rotated grid with a horizontal resolution of 0.27 • and with the North Pole at 48 • N and 176 • E. Such a rotated grid, with the equator running through the New Zealand domain, ensures a quasi-uniform grid box spacing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation